Increased production of IL-4 and IL-12p40 from bronchoalveolar lavage cells are biomarkers of Mycobacterium tuberculosis in the sputum. - Anna Nolan (PLoS ONE, 2013)
Tuberculosis (TB) causes 1.45 million deaths annually world wide, the majority of which occur in the developing world. Active TB disease represents immune failure to control latent infection from airborne spread. Acid-fast bacillus (AFB) seen on sputum smear is a biomarker for contagiousness.We enrolled 73 tuberculosis patients with extensive infiltrates into a research study using bronchoalveolar lavage (BAL) to sample lung immune cells and assay BAL cell cytokine production. All patients had sputum culture demonstrating Mycobacterium tuberculosis and 59/73 (81%) had AFB identified by microscopy of the sputum. Compared with smear negative patients, smear positive patients at presentation had a higher proportion with smoking history, a higher proportion with temperature >38.5(0) C, higher BAL cells/ml, lower percent lymphocytes in BAL, higher IL-4 and IL-12p40 in BAL cell supernatants. There was no correlation between AFB smear and other BAL or serum cytokines. Increasing IL-4 was associated with BAL PMN and negatively associated with BAL lymphocytes. Each 10-fold increase in BAL IL-4 and IL-12p40 increased the odds of AFB smear positivity by 7.4 and 2.2-fold, respectively, in a multi-variable logistic model.Increasing IL-4 and IL-12p40 production by BAL cells are biomarkers for AFB in sputum of patients who present with radiographically advanced TB. They likely reflect less effective immune control of pathways for controlling TB, leading to patients with increased infectiousness.